Assessment of tire chips as soil drains to mitigate liquefaction - Domingo, Edward John M.
Soil liquefaction is the phenomenon wherein soil loses its strength and stiffness as a response to cyclic loading. One established method for the mitigation of liquefaction is the installation of gravel drains. Gravel drains are stiff, granular columns that are placed under the surface of the soil. This study aims to assess if tire chip drains are a possible alternative to gravel drains. This is done by using a physical model with a shaking box and pendulum hammer set-up. Trials with no drains, gravel drains and tire chip drains are compared using their visual performance, settlements, and pore water pressure generation. A series of t-tests are used to determine if these values vary significantly. The two drain cases have performed well in the trials except for having larger settlements. This however is attributed to the method of drain installation in the study. With these results, we can conclude that tire chip drains are a viable alternative to gravel drains.